IDEAL in Meshes for Prolapse, Urinary Incontinence, and Hernia Repair. (October 2013) - Gerullis, Holger; Klosterhalfen, Bernd; Borós, Mihaly; Lammers, Bernhard; Eimer, Christoph; Georgas, Evagelos; Otto, Thomas
Purpose . Mesh surgeries are counted among the most frequently applied surgical procedures. Despite global spread of mesh applying surgeries, there is no current systematic analysis of incidence and possible prevention of adverse events after mesh implantation. Materials and Methods . Based on the recommendations of IDEAL an in vitro test system for biocompatibility of surgical meshes has been generated (Innovation). Coating strategies for biocompatibility optimization have been developed (Development). The native and modified alloplastic materials have been tested in an animal model over 2 years (Exploration and Assessment and Long-term study). Results . In 3 meshes, implanted in sheep and explanted at 4 different time points (a, 3 months; b, 6 months; c, 12 months; and d, 24 months) over 24 months, thickness of inflammatory tissue (TVT a, 35 µm; b, 32 µm; c, 33 µm; d, 28 µm; UltraPro, a, 25 µm; b, 24 µm; c, 21 µm; d, 22 µm; PVDF a, 20 µm; b, 21 µm; c, 14 µm; d, 15µm), connective tissue (TVT a, 37 µm; b, 36 µm; c, 43 µm; d, 41 µm; UltraPro a, 33 µm; b, 32 µm; c, 40 µm; d, 38 µm; PVDF a, 25 µm; b, 22 µm; c, 22 µm; d, 24 µm), and macrophage infiltration (TVT a, 36%; b, 33%; c, 23%; d, 20%; UltraPro a, 34%; b, 28%; c, 25%; d, 22%; PVDF a, 24%; b, 18%; c, 18%; d, 16%) revealed comparable ranking characteristics at every time point after explantation. The in vivo performance of these meshes in a sheep model was predictable with a previously developed in vitro test system. Coating of meshes with autologous plasma prior to implantation seems to have a positive effect on the meshes biocompatibility. Conclusion . We have applied IDEAL criteria on a new innovation for surgical meshes. The results permit the generation of a ranking of currently available meshes with potential to optimize future meshes.